Seizure frequency discrepancy between subjective and objective ictal electroencephalography data in dogs. (18th May 2021) - Ukai, Masayasu; Parmentier, Thomas; Cortez, Miguel A.; Fischer, Andrea; Gaitero, Luis; Lohi, Hannes; Nykamp, Stephanie; Jokinen, Tarja S.; Powers, Danielle; Sammut, Veronique; Sanders, Sean; Tai, Tricia; et al.
Abstract: Background: Many studies of epilepsy in veterinary medicine use subjective data (eg, caregiver‐derived histories) to determine seizure frequency. Conversely, in people, objective data from electroencephalography (EEG) are mainly used to diagnose epilepsy, measure seizure frequency and evaluate efficacy of antiseizure drugs. These EEG data minimize the possibility of the underreporting of seizures, a known phenomenon in human epileptology. Objective: To evaluate the correlation between reported seizure frequency and EEG frequency of ictal paroxysmal discharges (PDs) and to determine whether seizure underreporting phenomenon exists in veterinary epileptology. Animals: Thirty‐three ambulatory video‐EEG recordings in dogs showing ≥1 ictal PD, excluding dogs with status epilepticus. Methods: Retrospective observational study. Ictal PDs were counted manually over the entire recording to obtain the frequency of EEG seizures. Caregiver‐reported seizure frequency from the medical record was categorized into weekly, daily, hourly, and per minute seizure groupings. The Spearman rank test was used for correlation analysis. Results: The coefficient value ( r s ) comparing reported seizure to EEG‐confirmed ictal PD frequencies was 0.39 (95% confidence interval [CI] = 0.048‐0.64, P  = .03). Other r s values comparing history against various seizure types were: 0.36 for motor seizures and 0.37 for nonmotor (absence) seizures. Conclusions and Clinical Importance: A weak correlation was found between the frequency of reported seizures from caregivers (subjective data) and ictal PDs on EEG (objective data). Subjective data may not be reliable enough to determine true seizure frequency given the discrepancy with EEG‐confirmed seizure frequency. Confirmation of the seizure underreporting phenomenon in dogs by prospective study should be carried out.